NEW INNOVATIVE METHODS AND TECHNOLOGIES OF PRIMARY CLASS NATURAL SCIENCE TEACHING - Norova, Nargiza (MMIT Proceedings, 2023)
This article describes new innovative methods and technologies in teaching natural sciences to elementary school students. Comparative considerations related to their application during the lesson, analysis-synthesis of the results, and monitoring of the effectiveness of the lesson were conducted.